Evolução e perfil das exportações de empresas de pequeno porte brasileiras no contexto das políticas industriais dos anos 2000 - Sousa, Graciele de Fátima (2014)
The Micro and Small Enterprises (MSEs) are important for Brazil\'s economic development, due to the significant contribution to employment generation and the promotion of the country\'s socio-economic inclusion. In this way, the MSEs need a favorable environment for its strengthening, and thus, be able to contribute in a expressive way for the richness generation in Brazil, and have the opportunity of working in the international trade. The aim of this work is to outline a sectorial and regional profile of exports from the brazilian MSEs, in the period from 2002 to 2012, based on the recent analyses of industrial politics in Brazil that contain measures toward to MSEs, including measures for its internationalization through the exportation\'s optic. By the evolution of export indicators, it was possible to investigate the hypothesis that the trajectory of evolution on the MSEs\' export basket didn\'t change expressively, with the elaboration and implementation of measures, in order to promote the competitivity and MSEs\' export, contained in the industrial policies implemented since 2003. The analyses shows that from 2002 to 2012, have occurred some small modifications, but these weren\'t sufficient to change meaningly the following characteristics, outlined of the MSEs\' exports: i) the MSEs didn\'t increase their participation in Brazil\'s exportation total amount; ii) MSEs\' exportation are concentrated in the industry of low technology intensity, despite the occurrence of a certain diversification of the sectors; iii) there is a geographycal concentration in Brazil\'s South Region and South-East of exporter MSEs; iv) there is a concentration of external sales from MSEs for the American countries, especially, for Latin America. Is possible to conclude that, the maintenance of a sectorial and regional profile in MSEs\' exports, can be justified for the fact that these enterprises are still presenting a situation of low competitivity, requiring industrial policies measures in long term.